2006
DOI: 10.1189/jlb.0106024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of age-associated cytokine dysregulation in LPS-stimulated macrophages

Abstract: Aged humans and rodents are susceptible to infection with Streptococcus pneumoniae bacteria as a result of an inability to make antibodies to capsular polysaccharides. This is partly a result of decreased production of proinflammatory cytokines and increased production of interleukin (IL)-10 by macrophages (Mphi) from aged mice. To understand the molecular basis of cytokine dysregulation in aged mouse Mphi, a microarray analysis was performed on RNA from resting and lipopolysaccharide (LPS)-stimulated Mphi fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 62 publications
11
105
2
1
Order By: Relevance
“…Hence, the use of local anti-inflammatory agents to control airway inflammation may help to dampen respiratory allergies by preventing the recruitment of memory B cells. More importantly, aging has been associated with impaired inflammatory responses and TLR function (36)(37)(38), and our findings indicate that this might lead to poor memory B cell recruitment in aged individuals responding to infection.…”
Section: Discussionmentioning
confidence: 88%
“…Hence, the use of local anti-inflammatory agents to control airway inflammation may help to dampen respiratory allergies by preventing the recruitment of memory B cells. More importantly, aging has been associated with impaired inflammatory responses and TLR function (36)(37)(38), and our findings indicate that this might lead to poor memory B cell recruitment in aged individuals responding to infection.…”
Section: Discussionmentioning
confidence: 88%
“…The first transcriptional profiles of aging were generated in a limited number of mouse tissues such as muscle [27] and brain [28]. Recently, transcriptional profiles of such diverse organs as adipose tissue [29], heart [30], liver [31••], and macrophages [32] have been studied. A recent study by Edwards et al used an empirical Bayes approach to identify 712 transcripts that are age-regulated in mouse muscle that were enriched for genes active in the p53 proapoptotic pathway in addition to genes encoding mitochondrial proteins involved in energy generation [33].…”
Section: Dna Microarray Studies Of Aging In Micementioning
confidence: 99%
“…Overall, their data suggest that different loci contributed to variation in immune responses at each age, consistent with the mutation accumulation model of senescence. In mice, following LPS challenge, it was found that 500 genes were activated in macrophages from young and old individuals, but more than 150 were activated only in the old or only in the young (12).…”
Section: Human Longevity Genetics and Inflammationmentioning
confidence: 99%